Quantifying Medium Chain Fatty Acid Mitigation Activity Over Time against Porcine Epidemic Diarrhea Virus in Nursery Pig Diets - J. T. Gebhardt; J. C. Woodworth; M. D. Tokach; J. M. DeRouchey; R. D. Goodband; C. K. Jones; S. S. Dritz (Kansas Agricultural Experiment Station Research Reports, 2017)
Medium chain fatty acids (MCFA) are six to twelve carbon length molecules that have shown significant promise as potential mitigants of biological hazards in feed and feed ingredients. The use of residual duration of activity approaches, such as MCFA, have significant advantages compared to point-in-time mitigation strategies. The primary advantage of MCFA is the ability to mitigate the risks generated by post-processing contamination; however, the duration of mitigation activity has not been established. Therefore, the objective of this experiment was to characterize the mitigation properties of MCFA-treated swine feed 40 d following feed manufacturing. Treatments (n = 8) consisted of a dose response including 0, 0.25, 0.50, 1.0, and 1.5% dietary inclusion of a MCFA blend (1:1:1 ratio C6, C8, and C10) as well as 0.5% C6 alone, 0.5% C8 alone, or 0.5% C10 alone. Following feed manufacturing, feed was stored in bags at barn temperature and humidity for 40 d (June to July 2017). Following sampling after storage, subsamples were placed in separate high-density polyethylene bottles and inoculated with Porcine Epidemic Diarrhea Virus (PEDV) to achieve a final titer of 104TCID50/g. Separate sample bottles were analyzed on d 0 and 3 post-inoculation. A significant treatment × day interaction (P<0.001) was observed, where the cycle threshold (Ct) numerically increased over time in select treatments, and was numerically reduced in others. Means separation, adjusted to control experiment-wise error rate, did not indicate evidence of a difference within treatment among days of analysis (P>0.05) for any of the eight treatments. When evaluating increasing inclusion of MCFA blend, an inclusion level × day interaction was observed (quadratic, P = 0.023), where PEDV Ct values increased (quadratic, P = 0.001) on d 0 with increasing levels of MCFA blend inclusion also increased on d 3 (linear, P<0.001). On d 0 post-inoculation, the addition of C6, C8, or C10 alone resulted in significantly greater Ct values compared to no supplemented MCFA (P<0.05). The addition of 0.5% C6 and 0.5% C8 did not change Ct value (P>0.05) compared to 0.5% MCFA blend; however, adding 0.5% C10 resulted in a lower Ct value (P<0.05) compared to 0.5% MCFA blend. On d 3 post-inoculation, the addition of 0.5% C6 or 0.5% C10 resulted in greater Ct values compared to control (P<0.05), whereas, no improvement was observed with 0.5% C8 compared to control (P>0.05). The addition of 0.5% MCFA blend resulted in insufficient evidence of difference in Ct values compared to adding individual MCFA (P>0.05). In summary, treatment of feed with medium chain fatty acids retains mitigation properties for a significant period of time following feed manufacturing. Although we did not assess infectivity through bioassay, the data herein suggest a residual duration mitigation potential for MCFA well beyond feed manufacturing. Additional research characterizing the duration of activity beyond one point in time following feed manufacturing is warranted.
Keywords: medium chain fatty acid; mitigation; PEDV